Nutrition: The position in English to-day - M'Gonigle, G. C. M. (George Cuthberth Mura), -1939 (London : Industrial Christian Fellowship)
1936-11 1936 1930s 15 pages housing conditions improved, old age pensions provided, and other social reforms carried through. The tendency towards improvement has been continuous, but each step forward has been taken only when public opinion and the public conscience demanded that an advance should be made. Those, who first pointed to each evil and called for its remedy, were apt to be looked on as visionary enthusiasts contaminated with a spirit of impracticable idealism, and as meddling disturbers of the settled order of things as they are. Even to-day there are some who stigmatise those, who are striving to bring to the public notice the true facts of malnutrition in this country, as disruptive and disturbing elements in the public life. During recent years the public conscience has been disturbed about the nutritional state of the unemployed and lowly paid worker. This uneasiness is growing, but the public has been uncertain as to facts, and is not yet definitely convinced that the evil of malnutrition is a real evil of widespread incidence and of major importance. Sir John Orr in England, and writers dealing with the problem internationally on behalf of the League of Nations, have done much to throw the light of truth upon the subject but, unfortunately, their publications are not sufficiently widely read, and the daily press has not always been wise in its presentation of the data supplied on the subject. Modern scientific knowledge indicates that the nutritional factor constitutes the greatest single influence on the well- or ill-being of all animals, man included. Though the public is becoming conscious of nutrition as a factor of importance, people ask, not unreasonably, why it is only in very recent years that they have heard so much about it. Was there not mal- 4 15X/2/217/2